Autodesk 3ds max 2012 essentials - Derakhshani, Randi; Derakhshani, Dariush; ebrary, Inc. (Indianapolis, Ind. : Wiley Pub., 2011)
A guide to 3ds Max explains how to use the software to create a variety of animation, film effects, and games.
Includes index.
Includes bonus chapter.
Electronic reproduction.
Keywords: 3ds max (Computer file); Computer animation; Three-dimensional display systems; Electronic books